Putting the Price in Asset Pricing - CHO, THUMMIM; POLK, CHRISTOPHER (Journal of Finance, 2024)
ABSTRACT We propose a novel way to estimate a portfolio's abnormal price , the percentage gap between price and the present value of dividends computed with a chosen asset pricing model. Our method, based on a novel identity, resembles the time‐series estimator of abnormal returns, avoids the issues in alternative approaches, and clarifies the role of risk and mispricing in long‐horizon returns. We apply our techniques to study the cross‐section of price levels relative to the capital asset pricing model (CAPM) and find that a single characteristic, adjusted value , provides a parsimonious model of CAPM‐implied abnormal price.